2018
DOI: 10.1007/s11095-017-2341-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inadequate Temperature Storage Conditions on Aggregate and Particle Formation in Drugs Containing Tumor Necrosis Factor-Alpha Inhibitors

Abstract: PurposeTo measure aggregate and particle formation in tumor necrosis factor-alpha (TNF-α) inhibitors etanercept, adalimumab and certolizumab pegol product samples after exposure to freezing temperature conditions similar to storage conditions previously observed in patients’ homes.MethodsTNF-α inhibitors in their original primary and secondary packaging were exposed to 32 freeze-thaw cycles (−10°C for 120min/5°C for 60 min) or continuous low storage temperature (−20°C for 96 h) before thawing at 2–8°C. Non-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Subvisible particles are ubiquitous in formulations of therapeutic proteins, but their levels can be greatly increased by stresses encountered during shipping, handling, and storage. [42][43][44] Agitation stresses are incurred as a result of vibration during shipping and during routine handling of liquids. Although liquid formulations of therapeutic proteins are typically intended to remain in liquid form at controlled temperature, accidental freezing can occur, especially during shipping in containers cooled with gel packs, 38 or in formulations intended for home administration.…”
Section: Discussionmentioning
confidence: 99%
“…Subvisible particles are ubiquitous in formulations of therapeutic proteins, but their levels can be greatly increased by stresses encountered during shipping, handling, and storage. [42][43][44] Agitation stresses are incurred as a result of vibration during shipping and during routine handling of liquids. Although liquid formulations of therapeutic proteins are typically intended to remain in liquid form at controlled temperature, accidental freezing can occur, especially during shipping in containers cooled with gel packs, 38 or in formulations intended for home administration.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, simulation studies were carried out in the laboratory and the possible impact on the physicochemical properties of the proteins under these conditions was established. 117 Clearly, this issue of proper storage and handling of biologics in real-life situations needs more attention in educational programs for health care professionals and more hard data are urgently needed to assess the real risk patients run.…”
Section: Handling Of Biologics In Real-life Situationsmentioning
confidence: 99%
“…In a follow-up study, a few commercial protein pharmaceuticals in prefilled syringes were exposed to similar freeze-thaw cycles as those that were experienced in patients' refrigerators; the authors observed that the applied stress caused measurable increases in particle levels. 80 Whether such changes in the impurity profile have an impact on the overall safety and efficacy of the products remains to be studied, but potentially, they could contribute to immunogenicity in the patients receiving a product mishandled in such a way.…”
Section: Temperature Excursions and Freeze-thaw Cyclesmentioning
confidence: 99%